The Effect of Daily Use of Plantar Mechanical Stimulation Through Micro-Mobile Foot Compression Device Installed in Shoe Insoles on Vibration Perception, Gait, and Balance in People With Diabetic Peripheral Neuropathy - Kang, Gu Eon (J Diabetes Sci Technol, 2019)
OBJECTIVE: People with diabetic peripheral neuropathy (DPN) have impaired gait and balance performance. The aim of this study is to investigate therapeutic effectiveness of mechanical stimulation through a wearable foot compression device equipped in a shoe insole on vibration perception, balance control and gait performance in people with DPN. METHODS: Using a single-arm 4-week intervention study design, we examined effectiveness of daily use of shoes equipped with the foot compression device (Footbeat™, AVEX, Grand Junction, CO, USA) on improving vibration perception threshold (VPT(max)), skin perfusion pressure (SPP), ankle brachial index (ABI), lower extremities edema (circumferences in the calf and ankle), and motor performance (postural sway with eyes open and closed conditions, and gait performance during normal, dual-task and fast walking). Thirty people with type 2 diabetes and symptoms of PN completed the experimental protocol. RESULTS: Improvements in VPT(max) (before = 27.4 V, after = 23.3 V, P = .007, d = 0.33, where d denotes effect size), center-of-mass sway in the mediolateral direction with both eyes open and closed conditions (before = 0.94 cm, after = 0.76 cm, P = .020, d = 0.47; before = 1.10 cm, after = 0.83 cm, P = .033, d = 0.66, respectively), and stride velocity for normal walking, dual-task walking and fast walking tasks (before = 0.87 m/s, after = 0.96 m/s, P = .017, d = 0.41; before = 0.75 m/s, after = 0.91 m/s, P = .001, d = 0.77; before = 1.10 m/s, after = 1.20 m/s, P = .043, d = 0.33, respectively) were found post treatment. There was no significant improvement in SPP, ABI, and circumferences in the calf and ankle. CONCLUSIONS: Our findings suggest the wearable foot compression device may be effective for reducing neuropathic symptoms and enhancing motor performances in people with DPN.